Values of the Wedding Tradition of the Malay Tribe Ogan Ogan Komering Ulu in the Globalisation Era - Zamhari, Ahmad; ., Warto; Suryono, Hassan (KnE Social Sciences, 2024)
Local cultural diversity is a pillar of Indonesia’s national culture in the era of globalization. Efforts to maintain local culture need to re-instill values, one of which is the values of the Ogan tribal wedding tradition in the era of globalization which has become extinct due to technological and information developments. This research aims to explain again the stages of implementing the traditional rituals of the Ogan Malay wedding based on religion, kinship, togetherness, and courtesy. The problem is whether the values contained in the Ogan Malay wedding tradition. The approach used is a qualitative approach. Data were collected through the documentation method, and data analysis was done through direct observation in the field. The results of the research show that there are values contained in the wedding tradition of the Malay Ogan Ogan Komering Ulu tribe, South Sumatra in the era of globalization. Keywords: wedding tradition, Ogan Malay tribe, globalization era